P59 Predictors of renal survival in a cohort of patients with lupus nephritis with more than 30 years of follow-up. (23rd March 2020) - Farinha, Filipa; Pepper, Ruth J; Oliveira, Daniel G; McDonnell, Thomas; Isenberg, David A; Rahman, Anisur
Abstract : Background: Despite the improvement in survival of patients with lupus nephritis (LN) over the last decades, LN is associated with progression to end-stage renal disease (ESRD) in a significant proportion of patients. We aimed to investigate the factors influencing renal survival in patients with LN. Methods: Single-centre retrospective observational study. Patients with biopsy-proven proliferative, membranous or mixed LN were included. Individual clinical files were reviewed to obtain demographic, clinical, laboratory and pathological data. Cox regression analysis was performed to investigate predictors of progression to ESRD and Kaplan-Meier curves were obtained. Results: We studied 187 LN patients (135 proliferative, 38 membranous and 14 mixed LN), followed for up to 42 years (mean 13±9 years). Cumulative renal survival rates at 5, 10, 15 and 20 years were 93%, 85%, 78% and 70%, respectively. In univariable analysis, urinary protein/creatinine ratio (uPCR) above 42 mg/mmol or estimated glomerular filtration rate (eGFR) below 76 mL/min/1.73 m 2, one year after the diagnosis of LN, were the strongest predictors of progression to ESRD (figure 1 ), with hazard ratios (HR) of 8.081 [95%CI:1.856–35.179] and 4.985 [95%CI:1.964–12.651], respectively. HR for uPCR and eGFR at the time of diagnosis were considerably smaller (2.508 [95%CI:1.062–5.922] and 2.833 [95%CI:1.156–6.945] respectively). Other factors associated with increased risk of ESRD were Afro-Caribbean ethnicity (HR=3.861 [95%CI:1.817–8.206]), proliferative LN (HR=3.423 [95%CI:1.049–11.173]), not having taken antimalarials (HR=2.180 [95%CI:1.089–4.363]) and poorly controlled diastolic blood pressure (HR=1.016 [95%CI:1.001–1.030]). The effect of uPCR and eGFR at one year remained significant after adjusting for ethnicity, histological class, uPCR and eGFR at the time of diagnosis, use of antimalarials and diastolic blood pressure (table 1 ). Conclusions: uPCR above 42 mg/mmol and eGFR below 76 mL/min/1.73 m 2, one year after the diagnosis of LN, were the strongest predictors of progression to ESRD.